Digitalization and Designing a Medicinal Plants Web-based Information System for Supporting Herbal Tourism in Kima Bajo Village North Minahasa Regency - Rahman, Asep; Kalua, Aditya Lapu; Rompis, Lianly (Journal of Social Sciences and Technology for Community Service (JSSTCS), 2024)
Kima  Bajo  Village  is  one  of  the  villages  in  North  Minahasa  Regency  which  has  great  herbal tourism potential. In particular, Kima Bajo Village is known for having a wealth of knowledge about traditional medicine, especially coastal medicinal plants. Apart from that, Kima Bajo Village is a buffer area for the  Likupang  tourist  destination,  which  is  one  of  the  super  priority  destinations  (DSP).       Along  with technological  advances,  digitalization  has  become  a  solution  for  optimizing  tourism  potential. Digitalization of medicinal plants can increase the attractiveness of herbal tourism in Kima Bajo Village and its surroundings. Digitalization in the form of creating a digital database, has an important role in developing herbal tourism in Kima Bajo Village, North Minahasa Regency. In this case, digitalization has a  very  important  role  in  making  it  easier  to  access  information  and  understanding  about  medicinal plants, both for local people and tourists.      Our activity involved mapping the location and spatial distribution  of  these  medicinal  plants.  The  mapping  was  carried  out  based  on  the  position  of  the coordinate point where the medicinal plant population was found in the Kimabajo area.      The output of this activity was increasing public services regarding herbal tourism information in digital and web-based form. Apart from that, scientific publications, mass media publications and activity video publications were the output of the activity so that it can contribute optimally to partners and universities.